SINTESIS DAN KARAKTERISASI SILIKA GEL DARI ABU VULKANIK GUNUNG AGUNG MELALUI TEKNIK SOL-GEL - Utari, N. P. S. N.; Sudiarta, I W.; Suarya, P. (Jurnal Kimia (Journal of Chemistry); Vol.14 No.1 Januari 2020DO - 10.24843/JCHEM.2020.v14.i01.p06, 2020)
Mount Agung in Karangasem, Bali which erupted in September 2017 produced abundant volcanic ash. This ash can be used as a raw material for making silica gel. The stages of the research carried out included analysis of the content of silicon (Si), synthesis of silica gel using sol-gel technique, characterization using FTIR, X-RD instruments as well as surface acidity. The results of the analysis using the X-RD instrument showed the presence of silicon from SiO 2 found at 2? = 28,07530. The silica gel yield obtained in this study was 15.05% w/w. The results of the characterization with the FTIR instrument showed that silica gel from volcanic ash of Mount Agung had the main Si-OH and Si-O-Si groups. The hydroxyl bond from Si-OH grup were found at ±3649.32 cm -1 for stretching vibrations and ±1687,71 cm -1 for bending vibrations. Si-O bond from Si-O-Si group were found at ±1207.44 cm -1 for asymmetric stretching vibrations and ±482.20 cm -1 for bending vibrations. Diffractogram showed that the silica gel had an amorphous structure with surface acidity of 18.0222 mmol/g and a surface area of 36.5514 m 2 /g.  Keywords: Agung mountain, silica gel, sol-gel, vulcano ash